A day in the life of the United States Armed Forces photographed by 125 of the world's leading photojournalists on a single day, October 22, 2002 - Naythons, Matthew; Korman, Lewis J. (HarperCollins Publishers Inc., 2003)
A photographic documentary of American military life offers insight into the lives of the nation's elite units, new recruits, and MPs on outposts, strategic bases, and in the cockpits of fighter planes